Genome-wide mapping of the RNA targets of the Pseudomonas aeruginosa riboregulatory protein RsmN - Romero, Manuel; Silistre, Hazel; Lovelock, Laura; Wright, Victoria J.; Kok, Gan-Chan; Kar-Wai, Hong; Williams, Paul; Cámara, Miguel; Heeb, Stephan (Oxford University Press, 2018)
Pseudomonads typically carry multiple non-identical alleles of the post-transcriptional regulator rsmA. In P. aeruginosa, RsmN is notable in that its structural rearrangement confers distinct and overlapping functions with RsmA. However, little is known about the specificities of RsmN for its target RNAs and overall impact on the biology of this pathogen. We purified and mapped 503 transcripts directly bound by RsmN in P. aeruginosa. About 200 of the mRNAs identified encode proteins of demonstrated function including some determining acute and chronic virulence traits. For example, RsmN reduces biofilm development both directly and indirectly via multiple pathways, involving control of Pel exopolysaccharide biosynthesis and c-di-GMP levels. The RsmN targets identified are also shared with RsmA, although deletion of rsmN generally results in less pronounced phenotypes than those observed for ΔrsmA or ΔrsmArsmNind mutants, probably as a consequence of different binding affinities. Targets newly identified for the Rsm system include the small non-coding RNA CrcZ involved in carbon catabolite repression, for which differential binding of RsmN and RsmA to specific CrcZ regions is demonstrated. The results presented here provide new insights into the intricacy of riboregulatory networks involving multiple but distinct RsmA homologues.